The Analysis of Impoliteness Strategies Used in Students’ Social Interactions at Universitas Islam Makassar - Alfarabi, Ahmad Tika; Warsidi, Warsidi (English Literature Studi Program Universitas Islam Makassar, 2024)
This study aims to determine the strategy of impoliteness and the factors that influence the use of impolite expressions by students in social interactions at Makassar Islamic University. This research uses descriptive qualitative method with simple random sampling, and instruments in the form of audio recordings and interviews. Data analysis techniques include data reduction, data presentation, and conclusion drawing. The results showed that there were 22 data included in the incivility strategies, which included five strategies according to Culpeper: veiled incivility, positive incivility, negative incivility, sarcasm or feigned incivility, and withholding politeness. The most frequently used strategy is sarcasm or feigned incivility. In addition, there are five factors that cause incivility, namely social status, age difference, gender difference, social distance or familiarity, and situation. Incivility allows the expression of socially recognized views and can be an important factor in the development of peer-to-peer communication, so this concept of human values and the role of incivility requires further attention in research.